Optimization of Early Detection by Bhabinkamtibmas to Prevent Intolerance in the Temanggung Area - Fahridzal Hanafi (Tanggon Kosala, 2023)
Indonesia is a country with a lot of variety of plurality, there are a lot of conflict potention as the result of belief differences from the societies. One of the conflicts is Discrimination against minorities as a result of extreme intolerance. Intolerance is a feeling that came from someone or group of people who feels the difference is the root of problems and this kind of act is contrary with “Bhinneka Tunggal Ika”. Reform efforts can not lift the nation out from the circle of crisis. Pancasila as the state philosophy has been forgotten as if irrelevant to be included in the reform efforts, this kind of act leads to conflict outbreak in society. Some intolerance cases has occurred in Temanggung, like destruction of worship places. Repressive efforts to prevent intolerance not yet effective enough so the early detection activity is needed. Polri as the public servant need to make sure the security and public order can be maintained through Polmas (Community Policing). Therefore, Bhabinkamtibmas, as the forefront of Polmas function executive, has important role to prevent anarchist action as result of intolerance from the implementation of early detection. The purpose of this research is to know how far the implementation of Bhabinkamtibmas early detection. The research is using qualitative model with approaching the real case which the data retrieval come from interview, observation, documents study, and Focus Group Discussion (FGD) towards a number of sources in the jurisdiction of Temanggung Police Station’s area. The results of the research shows that Bhabinkamtibmas need to optimizing their ability of early detection from observation, searching information, and willingness to listen actively xvi towards society. It is compatible with Polri Transformation, especially the fifth program, “Stabilization of performance, maintenance of security and public order fr om predictive policing activity. Bhabinkamtibmas officers expected to be able upgrading their ability of data based early detection, information, and factual events. Therefore, Bhabinkamtibmas can give the situation mapping, also becoming the referral center of village information.